Rheumatic fever: New ideas in diagnosis and management - Lawrenson, John (SA Heart Journal, 2017)
Rheumatic heart disease remains a major cause of disability and death in developing countries. Careful re-analysis of mid-20th century data as well as the juxtaposition of well-funded research units and populations at risk have generated information that resulted in radical departures from standard approaches to the prevention, clinical recognition and treatment of acute rheumatic fever. As a result, rheumatic heart disease may be eliminated in the future.